1 - Private Surge amid Public Dominance in Higher Education: The African Perspective - Mabizela, Mahlubi (Journal of Higher Education in Africa, 2007)
This article lays a foundation for the debates that follow in the rest of the volume. It particularly focuses on the broad pertinent issues such as the historical develop- ment of private higher education in Africa. While we may largely talk about ‘pri- vate surge’, it argues that this may be a case of ‘resurgence’ as antecedents of private higher education existed at the same time as the establishment of public sector institutions or even before in some instances. The article also explores is- sues of the definition of private higher education as a way of preparing the reader to understand what the rest of the articles in the volume refer to when discussing the subject. It then discusses underlying factors in the establishment and growth of private higher education, pointing to issues that seem to be unique to the conti- nent and other developing countries. It then concludes by arguing that private higher education has a future in the continent, especially because it is required by the systems of higher education and the challenges and lessons this poses for governments. The article draws extensively from the rest of the articles in the volume, partly as a way of introducing their debates but also as an illustration of the richness of knowledge they contain, and it also draws from other international literature.